2012
DOI: 10.3233/wor-2012-0191-414
|View full text |Cite
|
Sign up to set email alerts
|

Physical demands during the hauling of fishing nets for artisan fishing using rafts in beach of Ponta Negra, Natal-Brasil

Abstract: The current article aims to analyse the activity and the repercussions in the health of the artisan fishermen who use rafts in the urban Beach of Ponta Negra in Natal -RN, with emphasis on the physical demands at the step of hauling the nets from the ocean. It has been taken as a reference the methodology of Work Ergonomic Analysis-WEA. 21 fishermen participated in the study (50% of the population). It was used applying observational techniques and methodologies (open and sistematic observations and simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Instead, this study has shown that safety measures to be applied should be developed according a Safety-II perspective (Hollnagel, 2014) focused in dampening potential output variability without hampering the system's adaptive behavior capabilities (Morel et al, 2008), because such fishermen's adaptive capacities are the source of the system safety and resilience. These findings are according to the previous recommendations coming from ergonomic field studies (Jaeschke, 2010;Jaeschke and Saldanha, 2012), and the Diegues' (2002) description of fishermen activity.…”
Section: Actions Descriptionsupporting
confidence: 86%
See 1 more Smart Citation
“…Instead, this study has shown that safety measures to be applied should be developed according a Safety-II perspective (Hollnagel, 2014) focused in dampening potential output variability without hampering the system's adaptive behavior capabilities (Morel et al, 2008), because such fishermen's adaptive capacities are the source of the system safety and resilience. These findings are according to the previous recommendations coming from ergonomic field studies (Jaeschke, 2010;Jaeschke and Saldanha, 2012), and the Diegues' (2002) description of fishermen activity.…”
Section: Actions Descriptionsupporting
confidence: 86%
“…The learning is done on the job. The apprentices follow the masters in the expeditions and begin to carry out the procedures, practices, and strategies, becoming initially bowman (helper) and then becoming a master or captain: "It is a difficult activity to learn … but with enough fishing time, the person learns and he only learns by going there" (Fisherman, Jaeschke and Saldanha, 2012). To be considered as a master or captain, a fisherman must master the navigation techniques that comprise: knowledge about the weather (rain, winds) and sea conditions (waves, tides, moons and winds), navigation and safety (management of the raft) involving the use of the rudder, placement of sails, engine, triangulation and location of fishing spots, and fishing techniques (laying, withdrawal and storage of fishing nets, identification and storage of fish), raft maintenance skills etc.…”
Section: Introductionmentioning
confidence: 99%
“…They commonly work in precarious labor environments, with increased workloads and exposure to factors that compromise health, such as stress, insufficient physical activity, and shifts when biological predisposition (chronotype) is not respected. Chronotype can influence sleep quality, labor productivity, social performance and disease development, such as cardiovascular and metabolic responses that are detrimental [1017].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, 95% of fishermen felt some pain in the last 7 days, with a high prevalence in the lumbar vertebral spine (71%), neck (57%), knees (52%), and ankles and feet (33%), and 100% in the last 12 months, with high prevalence in lumbar spine (81%) and knees (57%). 38 Similarly, a high prevalence of MSDs was reported among female artisanal fishermen in Saubara, Bahia, Brazil, where 95% occurred in any body part, 71% in the neck or shoulder, and 70% in distal upper limb. 39 The prevalence of MSDs was 84% in Turkey and 75% in Bangladesh.…”
Section: Cardiovascular Problemsmentioning
confidence: 85%
“…In addition, 11% of traumatic skin disorders were caused by marine creature stings. Musculo-skeletal problems Jaeschke and Saldanha, (2012) 38 Brazil 21…”
Section: Discussionmentioning
confidence: 99%